Quantitative Studies of Low Impact Development Literaturein China - SUN Shiqin; HOU Jingwei (Renmin Zhujiang)
In the perspective of core journals, and master's and doctoral theses, and based onthe literature about low impact development (LID)retrieved from the China National KnowledgeInfrastructure (CNKI), this paper analyzes the annual publication trends, source journals, topicdistributions,number of citation and keyword clustering of literature, and discusses the rules andtrend of quantitative research on LID in China by the methods of socioeconomics, ecology,mathematical modeling, and systematics & spatial optimization.The results show that: The quantityof literature about the LID since 2009 increases rapidly in China, with wider researchperspectives, larger research scales, deeper research goals, and better research system.Modelsand methods are diversified, but there are some shortcomings such as rely too much on models, andlimitations to scheme diversification. Subsequent research should focus on method systeminnovation, comprehensive application of disciplines, and comprehensive evaluation system toprovide the oretical support and practical reference for sponge city construction and studies of LID.